Microsupercapacitors: Direct Conversion of Fe2O3 to 3D Nanofibrillar PEDOT Microsupercapacitors (Adv. Funct. Mater. 32/2020). (7th August 2020) - Diao, Yifan; Lu, Yang; Yang, Haoru; Wang, Hongmin; Chen, Haozhe; D'Arcy, Julio M.
Abstract : Microsupercapacitors (μSCs) are electrochemical energy storage devices serving as alternatives to batteries in miniaturized portable electronics. In article number 2003394, Julio M. D'Arcy and co‐workers demonstrate a superior and cost‐effective route for developing 3D μSCs that directly convert Fe2 O3 to poly(3, 4‐ethylenedioxythiophene) (PEDOT) nanofibers in one step. A vertically aligned PEDOT electrode possesses exceptional conductivity (3580 S cm −1 ) and results in a device exhibiting one of the highest energy densities (400 F cm −3 ) reported among organic μSCs.